The effect of a credit policy change on microenterprise upward transition and growth: evidence from Indonesia - Ilmiawan Auwalin, - (Springer International Publishing AG, 2020)
This paper attempts to establish a causal relationship between a government micro and small enterprises (MSEs) credit promotion policy and MSEs’ upward transitions and growth. Indonesian firm level data in conjunction with the cancellation of a mandatory MSE credit policy in 2001 by the Indonesian government are employed in the analysis. Firstly, estimations of the year-on-year micro to small size category transitions indicate the negative effect of the policy change on the upward transition of micro firms. Secondly, causal effect analysis using difference-in-differences (DiD) estimation, by employing the policy change as an exogenous shock on the MSE credit availability and setting medium and large enterprises (MLEs) as the counterfactual group, suggests that the policy cancellation reduces the probability of a micro firm to become a small firm by 1.3% relative to the MLEs’ probability of transitioning between size categories. The negative effect on turnover growth is also identified.